Buildings on Veer Nariman Marg - Ghosh, Ayan (2023)
The row of buildings located along Veer Nariman Marg (former Churchgate Street), facing the St. Thomas Cathedral. Seen from right to left, Elphinstone Building, Brady House, and HSBC Building. Horniman Circle used to be (and still is) the main financial and business hub of Mumbai and is home to several banks, high-end stores, and commercial offices.